2017
DOI: 10.1001/jamainternmed.2017.0906
|View full text |Cite
|
Sign up to set email alerts
|

Emergency Department Query for Patient-Centered Approaches to Sexual Orientation and Gender Identity

Abstract: and The Joint Commission recommend routine documentation of patients' sexual orientation in health care settings. Currently, very few health care systems collect these data since patient preferences and health care professionals' support regarding collection of data about patient sexual orientation are unknown.OBJECTIVE To identify the optimal patient-centered approach to collect sexual orientation data in the emergency department (ED) in the Emergency Department Query for Patient-Centered Approaches to Sexual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
115
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 125 publications
(118 citation statements)
references
References 25 publications
3
115
0
Order By: Relevance
“…535429 . In contrast, consistent with surveys of older LGBTQ patients, almost half our participants indicated they would be comfortable answering physician questions regarding their sexual orientation 5556 . Given the increased HIV and STI risk among AMSM, health care providers cannot afford to wait for young patients to raise the subject, since as our study and prior research indicates adolescents often do not disclose information critical to sexual health for fear of practitioner bias and do not view health care providers as a primary source for sexual health information 474557 .…”
Section: Resultssupporting
confidence: 61%
“…535429 . In contrast, consistent with surveys of older LGBTQ patients, almost half our participants indicated they would be comfortable answering physician questions regarding their sexual orientation 5556 . Given the increased HIV and STI risk among AMSM, health care providers cannot afford to wait for young patients to raise the subject, since as our study and prior research indicates adolescents often do not disclose information critical to sexual health for fear of practitioner bias and do not view health care providers as a primary source for sexual health information 474557 .…”
Section: Resultssupporting
confidence: 61%
“…Fifty-three patient participants and 26 provider participants were interviewed, details of whom have been reported previously 12. Demographics are provided in table 1.…”
Section: Resultsmentioning
confidence: 99%
“…However, to ensure successful implementation of SO/GI collection, it is important to understand the perspectives of key stakeholders, which include patients and providers. In a previous report,12 we demonstrated that patients and providers have divergent views on the importance of collecting this information. While we have recently published brief initial qualitative findings from the initial phase used to inform the overall project strategy,12 the purpose of this current report is to provide in-depth exploration of patient and provider perspectives concerning the importance of collection of patient SO/GI in the ED.…”
Section: Introductionmentioning
confidence: 80%
See 1 more Smart Citation
“…In this edition of EMJ , Kodakek4 and her team from the EQUALITY (Emergency Department Query for Patient Centered Approaches to Sexual Orientation and Gender Identity) mixed methods multiphase study5 in the USA examined the vast discrepancy between patient and healthcare professional attitudes towards routinely collecting information about GI and SO. Their qualitative investigation revealed a majority affirmation by patients that these questions should be asked.…”
mentioning
confidence: 99%